Inhibition of specific signaling pathways rather than epigenetic silencing of effector genes is the leading mechanism of innate tolerance - Masyutina, Anna M.; Maximchik, Polina V.; Chkadua, Georgy Z.; Pashenkov, Mikhail V. (Frontiers in Immunology, 2023)
Macrophages activated through a pattern-recognition receptor (PRR) enter a transient state of tolerance characterized by diminished responsiveness to restimulation of the same receptor. Signaling-based and epigenetic mechanisms are invoked to explain this innate tolerance. However, these two groups of mechanisms should result in different outcomes. The epigenetic scenario (silencing of effector genes) predicts that activation of a PRR should broadly cross-tolerize to agonists of unrelated PRRs, whereas in the signaling-based scenario (inhibition of signaling pathways downstream of specific PRRs), cross-tolerization should occur only between agonists utilizing the same PRR and/or signaling pathway. Also, the so-called non-tolerizeable genes have been described, which acquire distinct epigenetic marks and increased responsiveness to rechallenge with the same agonist. The existence of such genes is well explained by epigenetic mechanisms but difficult to explain solely by signaling mechanisms. To evaluate contribution of signaling and epigenetic mechanisms to innate tolerance, we tolerized human macrophages with agonists of TLR4 or NOD1 receptors, which signal via distinct pathways, and assessed responses of tolerized cells to homologous restimulation and to cross-stimulation using different signaling, metabolic and transcriptomic read-outs. We developed a transcriptomics-based approach to distinguish responses to secondary stimulation from continuing responses to primary stimulation. We found that macrophages tolerized with a NOD1 agonist lack responses to homologous restimulation, whereas LPS-tolerized macrophages partially retain the ability to activate NF-κB pathway upon LPS rechallenge, which allows to sustain low-level expression of a subset of pro-inflammatory genes. Contributing to LPS tolerance is blockade of signaling pathways required for IFN-β production, resulting in ‘pseudo-tolerization’ of IFN-regulated genes. Many genes in NOD1- or TLR4-tolerized macrophages are upregulated as the result of primary stimulation (due to continuing transcription and/or high mRNA stability), but do not respond to homologous restimulation. Hyperresponsiveness of genes to homologous rechallenge is a rare and inconsistent phenomenon. However, most genes that have become unresponsive to homologous stimuli show unchanged or elevated responses to agonists of PRRs signaling via distinct pathways. Thus, inhibition of specific signaling pathways rather than epigenetic silencing is the dominant mechanism of innate tolerance.